Letramento racial crítico e intersecção com gênero nas aulas de língua inglesa no curso formação de docentes. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The present research was carried out in a public school in Paraná, with three students from the 3rd year of the Teacher Training Course as participants. This work had as objectives: to verify, through autobiographical narratives, the perception of race and gender of the 3rd year students of the Teacher Training Course, and to make Bilingual Teaching Unit with suggestions for activities related to race and gender that would help in the pedagogical practices and in the teacher training of the students of the Teacher Training Course. Therefore, I tried to answer the research questions: 1) What do autobiographical narratives reveal about the perception of teachers in training about race and gender? 2) How the preparation of Bilingual Teaching Unit with suggestions for activities about race and gender can contribute to the training of teachers. Theoretically, the study was supported by authors such as Faria (2016), Tanuri (2000), Gadotti (2004), Saviani (2009), Luckesi (2005), among others who dedicate their studies to teacher training. For reflections on reflective teacher and reflective teacher in action, researchers such as Pimenta (2002) and Schön (1991) were used. On the perspective of teaching from Critical Racial Literacy, according to studies by Ferreira (2006, 2014, 2015). On theoretical reflections on race with gender intersection, I drew on research carried out by Auad (2006), Cavalleiro (2018), Crenshaw (1989, 2002, 2013) and Anti-racist Education: Cavalleiro (2001) and Ferreira (2012). The methodology used in this research is qualitative, ethnographic, and interventional. The instruments for data collection were field diary, questionnaire, autobiographical narratives and reflective questions carried out during the preparation of the Bilingual Teaching Unit. The results indicate that the students, through readings, discussions and reflections on race and gender, understand the importance of working in the classroom on the theme of race and gender, as well as Critical Racial Literacy is of extreme theoretical relevance for development of critical and reflective pedagogical practices and an important tool in anti-racist teacher training. The production of the Bilingual Didactic Unit by the undergraduate students is a good start for a critical reflection on the importance of bringing these discussions about race and gender, in an interdisciplinary way, to the school context.
Keywords: Letramento Racial Crítico; Língua Inglesa; Formação de Docentes; Gênero; Narrativas Autobiográficas; Critical Racial Literacy; English Language; Teacher Education; Gender; Autobiographical Narratives; CNPQ::LINGUISTICA, LETRAS E ARTES::LINGUISTICA